KEABSAHAN KEGIATAN DISTRIBUTOR DALAM PERSFEKTIF HUKUM PERDATA - Thomas Abbon (Fakultas Hukum Universitas Kristen Indonesia, 2017)
Abstract About distributors can be stated that up to now there has not been speci cally regulated provisions regarding distributors. The provisions regarding agency and distributor tend to be regulated in various regulations, which do not clearly distinguish the position, duties and functions between the agent and distributor. In order to create a conducive climate in the eld of economic activity, especially marketing activities, it is necessary to speci cally regulate everything related to agency and distributor activities by providing a difference between agents and distributors. Keywords: speci cally regulated; agency and distributor; marketing activities.